Echoes in memory: the lasting imprint of adult experiences from environmental education in fifth grade - Gal, Adiv (Frontiers in Education, 2025)
The study examines what adults remember from their participation in the program in fifth grade and explores the extent to which these memories and experiences are associated with their environmental values and attitudes in adulthood. A qualitative approach was employed using autobiographical narratives gathered through semi-structured interviews. Participants, aged 30 and above, were recruited via snowball sampling, and thematic analysis identified key patterns in their recollections. Five main themes emerged: experiential learning fosters long-term memories, collaboration enhances engagement, bridging theory and practice strengthens learning, the program cultivated self-efficacy, and environmental values persisted into adulthood. The study highlights the lasting effects of experiential environmental education. Although several participants reported a sustained emotional connection and heightened ecological awareness, few offered concrete examples of long-term pro-environmental behaviors in their adult lives. Findings point to the importance of long-term reinforcement in supporting pro-environmental behaviors, suggesting that structured follow-ups and continued engagement may help strengthen the long-term impact of such programs, although further research is needed to clarify this relationship.